Analisis Gaya Kepemimpinan, Beban Kerja, Lingkungan Kerja terhadap Kinerja Karyawan dan Kepuasan Kerja sebagai Variabel Intervening (Studi Empiris pada PT. Simone Accessary Collection) - Eva Aryanti; Eko Riyanto; Suyanto Suyanto (J-MAS (Jurnal Manajemen dan Sains), 2022)
The company is an organization consisting of several groups of individuals, where they work together with each other and carry out various activities that have been planned, to achieve the results of the goals that have been planned. In carrying out or completing these various activities, of course human resources will be involved as a means of supporting the completion of the company's activities. The research was conducted at PT. Simone Accesarry Collection Bogor. By taking a sample of 100 respondents as a research sample, which is calculated using the Slovin formula from a total population of 2,000 at a margin of error of 10%. Collecting data using a questionnaire, five measurement scales from strongly disagree to strongly agree, with an ordinal scale. The research was carried out quantitatively, as an analytical tool used Statistical Package for the Social Sciences SPSS version 20 analysis, while hypothesis testing was carried out with t-test and sig 0.05. The study produced ten main findings in accordance with the proposed hypothesis, namely the first path test in the study concluded that the influential and significant impact was between: Leadership Style, Workload, and Work Environment on Job Satisfaction. Leadership Style, Workload, and Job Satisfaction on Employee Performance. Work environment has a positive but not significant effect on employee performance. The second line of research in the study concludes that job satisfaction can moderate the Leadership Style, Workload, and Work Environment on Employee Performance through Job Satisfaction.